UKP (Indonesian Translators’ Qualification Exam) in Relation to Legal Translation Practice in Indonesia Its History, Roles, Debates and Challenges - Dewi, Haru Deliana (UI Scholars Hub, 2017)
This paper aims to describe the history and roles of UKP (Indonesian Translators’ Qualification Examination) in relation to legal translation practice in Indonesia and to discover the debates and challenges of this certification test. The method applied is a qualitative method, and the data were obtained from primary data via questionnaires and in-depth interviews, and from secondary data, such as from some published books, articles, and online sources. The results of the study are expected to provide a preliminary and comprehensive explanation of all matters related to UKP. As academic sources discussing this type of exam are not easily found, this paper could be one of the fruitful references on this topic.